Treatment strategies and predicting lymph node metastasis in elderly patients with papillary thyroid microcarcinoma. Issue 18 (7th May 2021) - Li, Wenhan; Tang, Yao; Li, Jianhui; Han, Wei; Wang, Danfang; Wang, Yongheng
Abstract : Abstract: This study aims to explore the prognostic variables for elderly papillary thyroid microcarcinoma (PTMC) patients as well as create a nomogram that could predict the occurrence of cervical lymph node metastasis (CLNM) on the basis of a large population database with high quality. A total of 5165 PTMC patients from Surveillance, Epidemiology, and End Results database database were enrolled in the study. In the meantime, we retrospectively collected 205 PTMC patients who underwent thyroidectomy in our medical center as an external control to test the accuracy of the model. The independent predictors of survival were identified by multivariate Cox regression analysis. Risk factors were selected as nomogram parameters to develop a model to predict CLNM. The C-index and calibration plots were used to evaluate CLNM model discrimination. The predictive nomogram was further validated in the external validation set. 76.8% of the enrolled patients underwent thyroidectomy. Overall survival and cancer-specific survival were significantly better in patients who underwent surgery than in those who did not ( P  < .001). Sex, tumor size, and extent of tumor were included in a multivariable logistic regression model to predict lymph node metastasis. The nomogram had good discrimination with a C-index of 0.71. The calibration curves showed perfect agreement between nomogram predictions and actual observations. Elderly PTMC patients who received a surgical approach without radiotherapy showed survival advantage than those with other treatment strategies. Moreover, a nomogram model was established to predict the risk of CLNM, which will help clinicians in making treatment decisions.